2009
DOI: 10.1159/000226240
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Sputum Mature Dendritic Cells in Healthy Smokers and Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background: Asthmatics who smoke have decreased pulmonary mature dendritic cells (DCs). Chronic obstructive pulmonary disease (COPD) patients have an increased amount of pulmonary immature DCs. We hypothesized that healthy smokers and patients with COPD have decreased pulmonary mature DCs. Methods: We identified sputum DCs expressing the maturation markers CD83 and DC-lysosome associated membrane protein (DC-LAMP) and DC subpopulations (i.e. myeloid and plasmacytoid DCs) by flow cytometry in healthy smokers be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 68 publications
0
14
0
1
Order By: Relevance
“…Cigarette smoke exposure could induce IL-10 production through the upregulation and activation of TLR4 and TLR9 on lung CD8 T cells from patients with COPD 31. The number of mucosal mature dendritic cells that produce IL-10 was decreased in healthy smokers and current smokers with COPD,32 33 and this might reduce IL-10 concentrations in the airways. In addition, kynurenine induces the development of tolerogenic dendritic cells14 and the differentiation of CD4 T cells towards Treg cells15 through the interaction with aryl hydrocarbon receptors that results in the induction of IL-10 and tryptophan catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke exposure could induce IL-10 production through the upregulation and activation of TLR4 and TLR9 on lung CD8 T cells from patients with COPD 31. The number of mucosal mature dendritic cells that produce IL-10 was decreased in healthy smokers and current smokers with COPD,32 33 and this might reduce IL-10 concentrations in the airways. In addition, kynurenine induces the development of tolerogenic dendritic cells14 and the differentiation of CD4 T cells towards Treg cells15 through the interaction with aryl hydrocarbon receptors that results in the induction of IL-10 and tryptophan catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…As, traditionally, the major activity of CD8 + T lymphocytes has been considered the facilitation of the rapid resolution of acute viral infections, the lower percentage of CD8 + T-cells suggests that smokers have a deficit in cell-mediated immunity in the lung, a site critical in the first-line defence against infection, and may explain the increased susceptibility of smokers for viral infections. Furthermore, previously our group has demonstrated that the expression of sputum dendritic cells maturation markers in smokers is decreased, which may significantly affect the ability of dendritic cells to induce effective immune responses, altering the lymphocyte subset population and therefore render smokers more susceptible to respiratory tract infections [28]. Moreover, after 12 months smoking cessation sputum macrophages decreased and neutrophils significantly increased among those who had quit.…”
Section: Discussionmentioning
confidence: 99%
“…They quantified CD83 expression semiquantitatively and found that CD83+ cells were located mainly in subepithelial areas of the airway wall [7]. More recently, in induced sputum samples, the same group [9] confirmed that COPD patients showed a decrease in mature DC counts, which was present even in current smokers with normal lung function and was reversed by smoking cessation. In a previous study in which mature DCs were identified by electron microscopy, current smokers with COPD showed a decreased number of bronchial mucosal DCs in bronchial biopsies [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations indicate an incomplete DC maturation process in the small airways of patients with COPD, with a decrease in mature (CD83+) DCs and an increase in langerin-expressing (CD207)+ DCs considered to be immature [6,7,8]. Moreover, active cigarette smoking was associated with decreased numbers of bronchial mucosal DCs expressing the maturation marker CD83 in induced sputum samples from COPD patients, and in endobronchial biopsies from asthmatic subjects [9,10]. …”
Section: Introductionmentioning
confidence: 99%